The significance of baroreflex sensitivity in hypertensive subjects with stroke - Čelovská, D; Stasko, J; Gonsorčík, J; Diab, A (Physiological research, 2010)
The relationship between baroreflex sensitivity expressed in ms/mm Hg (BRS) or in Hz/mm Hg (BRSf) in hypertensives with stroke in comparison with a group of stroke-free patients was evaluated. Twenty-six patients (aged 66+/-10 years, 11 females/ 15 males) with a history of the first ever ischemic stroke (6 months and more after stroke onset), which was neuroradiologically confirmed, were studied. These were compared to 30 hypertensive patients without history of any cardiovascular event, being of similar age and sex. BRS and BRSf were determined by the sequence and spectral methods (five-minute non-invasive beat-to-beat recording of blood pressure and inter-beat interval, controlled breathing at a frequency of 0.1 Hz). A significant negative correlation between spontaneous BRS and blood pressure (BP) represented by the grade of hypertension was present (r = -0.52, p<0.001). Differences between hypertensives with and without stroke were detected in BRS obtained by the spectral method (BRS spect p=0.0237, BRSf spect p=0.0285) or BRS obtained by sequence method (BRS seq p=0.0532, BRSf seq p=0.0273). The greatest decline in BRS values was in hypertensive stroke patients with metabolic syndrome, who had BRS values below 3 ms/mm Hg. We found out that BRS and BRSf were more impaired in stroke patients with essential hypertension even 6 months and more after stroke onset than in stroke-free hypertensive patients. This finding was independent of age-dependent decrease of BRS. Examination of baroreflex sensitivity as a marker of autonomic dysfunction along with global cardiovascular risk stratification of individuals seems to be a method for identifying patients at high residual cardiovascular risk.
Keywords: hodnocení rizik; Male; hypertenze; Slovakia; Risk Assessment; Slovenská republika; Risk Factors; regresní analýza; Autonomic Nervous System; Heart Rate; cévní mozková příhoda; Adult; Stroke; Aged; dospělí; Baroreflex; mužské pohlaví; senioři; srdeční frekvence; Case-Control Studies; Hypertension; Severity of Illness Index; Time Factors; autonomní nervový systém; senioři nad 80 let; lidé; krevní tlak; ženské pohlaví; studie případů a kontrol; Humans; časové faktory; rizikové faktory; Blood Pressure; Aged, 80 and over; Regression Analysis; stupeň závažnosti nemoci; Female; baroreflex; lidé středního věku; Middle Aged